2021
DOI: 10.1177/14034948211027816
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality in informal care research: a scoping review

Abstract: Aim: Informal caregivers share common experiences in providing care to someone with health and/or social needs, but at the same time their experiences differ across diverse backgrounds such as gender, age, culture, as these aspects of diversity co-shape these experiences. This scoping review aims to explore how aspects of diversity, across their intersections, are currently incorporated in informal care research and discusses how an intersectional perspective can further develop our understanding of informal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Education, although frequently reported in demographics, was also rarely considered as an important factor in informing intervention design and recruitment. Women with lower education are more likely to assume caregiving roles than those who have had additional educational opportunities [ 11 ]. Lower literacy levels among caregivers can affect their ability to navigate the health system and locate appropriate support for themselves and their care recipient [ 70 ], factors that can directly influence the design and usability of mHealth interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Education, although frequently reported in demographics, was also rarely considered as an important factor in informing intervention design and recruitment. Women with lower education are more likely to assume caregiving roles than those who have had additional educational opportunities [ 11 ]. Lower literacy levels among caregivers can affect their ability to navigate the health system and locate appropriate support for themselves and their care recipient [ 70 ], factors that can directly influence the design and usability of mHealth interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies had samples primarily made up of women, validating the literature that suggests women are most likely to provide caregiving support, corroborating cultural norms across a range of identities [ 76 ]. However, these studies did not address how intersecting identities (eg, culture, gender, race and ethnicity, and socioeconomic status) might shape expectations and responsibilities within a caregiving role [ 11 , 12 , 68 ]. Research suggests that culture strongly affects caregiving but that cultural influences on the caregiver role must be understood within the context of race and gender socialization [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, further research efforts should be placed on investigating the diversity among informal caregivers. In a recent scoping review, Hengelaar et al (2021) suggested employing an intersectional perspective in caregiver research that would account for various caregiver and care-receiver characteristics. That is, accounting for the diversity in the caregiver and care-receiver as well as the various contextual factors such as historical, cultural, and societal influences.…”
Section: Exploring Diversitymentioning
confidence: 99%
“…This study uses an innovative approach by not solely focusing on cultural aspects or differences but by going a step further and explore the in uence of intersecting aspects of diversity in the context of care networks (Bowleg, 2021). By doing so, diversity is understood as challenging inequalities and structural disadvantages within care networks (Hengelaar et al 2021).…”
Section: Introductionmentioning
confidence: 99%